I have encountered the following problem:

Determine whether $$\sum \limits_{n=0}^{\infty} \left(\sqrt[3]{n^3+1} - n\right)$$ converges or diverges.

What I have tried so far:

Assume that $a_n = \sqrt[3]{n^3+1} - n$.

  • $n$th term test: $\lim \limits_{x\to\infty} a_n = 0$ $\Rightarrow$ inconclusive.
  • $p$-series test: can't be used
  • geometric series test: can't be used
  • alternating series test: not alternating, can't use
  • telescoping series: does not look like it (after rewriting first few terms)
  • integral test: integrating the $a_n$ is outside the scope of my course (checked result with wolfram)
  • ratio test: simplification of the limit is not possible due to number of expanding terms
  • comparison / limit comparison test: no idea what should I compare it to

I would be grateful for any help.

  • 6
    $\begingroup$ Recall that $$\forall a,b\in \mathbb R\left(a^3-b^3=(a-b)\left(a^2+ab+b^2\right)\right).$$ Find $$\forall n\in \mathbb N\left(\root 3\of {n^3+1}-n=\dfrac{1}{\root 3\of {n^3+1}^2+n\root 3\of {n^3+1}+n^2}\right)$$ and compare. $\endgroup$ – Git Gud May 18 '15 at 10:18

Hint We can apply a cubic analogue of the technique usually called multiplying by the conjugate, which itself is probably familiar from working with limits involving square roots. In this case, write $$u = \sqrt[3]{n^3 + 1},$$ so that $$u^3 - n^3 = (n^3 + 1) - (n^3) = 1.$$ On the other hand, factoring gives (in analogy to the difference of perfect squares factorization $a^2 - b^2 = (a - b)(a + b)$ used in the square root case case) $$u^3 - n^3 = (u - n) (u^2 + un + n^2).$$

Explicitly, multiplying gives that we can write our sum as \begin{align} \sum_{n = 0}^{\infty} (u - n) &= \sum_{n = 0}^{\infty} (u - n) \cdot \frac{u^2 + un + n^2}{u^2 + un + n^2} \\ &= \sum_{n = 0}^{\infty} \frac{u^3 - n^3}{u^2 + un + n^2} \\ &= \sum_{n = 0}^{\infty} \frac{1}{u^2 + un + n^2} . \end{align} Now, $u > n$, and so the summand satisfies $$\frac{1}{u^2 + un + n^2} < \frac{1}{3 n^2}.$$ Hence, by the comparison test, the given series is bounded by $$\frac{1}{3} \sum_{n = 0}^{\infty} \frac{1}{n^2},$$ which converges by, e.g., the $p$-test.




$\sqrt[3]{n^3+1} = n\sqrt[3]{1+1/n^3}$, and then $\sqrt[3]{1+1/n^3} = 1 + \frac{1}{3n^3} + o(\frac{1}{n^3})$.

Next, I belive, limit comparison test will work.


For any $x\in[0,1]$, the inequality: $$ (1+x)^{\frac{1}{3}}\leq 1+\frac{x}{3} \tag{1}$$ holds by concavity or just by considering the cube of both terms. It follows that: $$ 0\leq \sqrt[3]{1+n^3}-n = n\left(\sqrt[3]{1+\frac{1}{n^3}}-1\right)\leq\frac{1}{3n^2}\tag{2}$$ hence the given series is convergent by the p-test or by the inequality: $$ 0\leq \sum_{n=1}^{N}\frac{1}{n^2} \leq 1+\sum_{n=1}^{N-1}\frac{1}{n(n+1)}=2-\frac{1}{N}\leq 2.\tag{3}$$


\begin{align*} \sqrt[3]{n^3+1}-n&=\frac{\left(\sqrt[3]{n^3+1}-n\right)\left(\sqrt[3]{(n^3+1)^2}+n\sqrt[3]{(n^3+1)}+n^2 \right )}{\left(\sqrt[3]{(n^3+1)^2}+n\sqrt[3]{(n^3+1)}+n^2 \right )}\\ &=\frac{1}{\left(\sqrt[3]{(n^3+1)^2}+n\sqrt[3]{(n^3+1)}+n^2 \right )}\\ &\le\frac{1}{3n^2}, \end{align*} so by direct comparison, your series converges.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.